2018
DOI: 10.36253/978-88-6453-795-5
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural Meteorology and Climatology

Abstract: Agricultural Meteorology and Climatology is an introductory textbook for meteorology and climatology courses at faculties of agriculture and for agrometeorology and agroclimatology courses at faculties whose curricula include these subjects. Additionally, this book may be a useful source of information for practicing agronomists and all those interested in different aspects of weather and climate impacts on agriculture. In times when scientific knowledge and practical experience increase exponentially, it is n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…Combined models reduced the magnitude of all the prediction error metrics to near acceptable levels. Although an error (MAPE or RPE) up to 20% is acceptable for setting dosage rates in the veterinary pharmaceutical industry [ 42 ], an error of more than 10% can be problematic [ 43 , 44 , 45 ] in other agricultural fields. In this study, values were approximately 9% to 12% for liveweight alone models and 8% to 10% for the combined models.…”
Section: Discussionmentioning
confidence: 99%
“…Combined models reduced the magnitude of all the prediction error metrics to near acceptable levels. Although an error (MAPE or RPE) up to 20% is acceptable for setting dosage rates in the veterinary pharmaceutical industry [ 42 ], an error of more than 10% can be problematic [ 43 , 44 , 45 ] in other agricultural fields. In this study, values were approximately 9% to 12% for liveweight alone models and 8% to 10% for the combined models.…”
Section: Discussionmentioning
confidence: 99%
“…Since changes in temperatures and precipitation significantly affect the biosphere (e.g., Lalić et al, 2018), viticulture as an important economic branch in the moderate latitudes (e.g., mainly between 35° and 55°; Jones, 2006) is strongly influenced by climate change (e.g., Bock, Sparks, Estrella, & Menzel, 2013; Fraga, García de Cortázar Atauri, Malheiro, Moutinho‐Pereira, & Santos, 2017; Koufos, Mavromatis, Koundouras, & Jones, 2018; Orlandini, Di Stefano, Lucchesini, Puglisi, & Bartolini, 2009). A number of recent studies (e.g., Fraga et al, 2016; Garnier, Daux, Yiou, & de Cortazar‐Atauri, 2011; Menzel, 2005; Webb et al, 2012) have shown that the phenological phases of grapevines, as well as grapevine yields and quality, are greatly influenced by temperature increases.…”
Section: Introductionmentioning
confidence: 99%
“…Very probably, ground water level will play an extremely important role in this process. It is generally accepted that climate change may most severely influence ground water table level under the conditions of sandy soils (Lalic et al 2018), which is the case of the region of our research. The interaction of climatic and hydrological factors with site-specific and geomorphological conditions on windblown sands at Záhorie may have a substantial impact on Scots pine growth and prosperity.…”
Section: Discussionmentioning
confidence: 79%